Premixed combustion and emission characteristics of methane diluted with ammonia under F-class gas turbine relevant operating condition - Zhang, Yanfei; Zhao, Dapeng; Li, Qin; Huang, Mingming; Hao, Qing; Du, Jianji; Song, Yang; Ming, Zhaoqing; Wang, Jihang (Frontiers in Energy Research, 2023)
Ammonia has been used on a small scale in other industrial equipment, such as gas turbines, as a carbon-free fuel. However, ammonia fuel suffers disadvantages such as high ignition temperature, low flame velocity and high NOx emissions. Doping with ammonia using a more reactive fuel, such as methane, can solve the above problems. Therefore, under the relevant operating conditions of the gas turbine (T = 723 K, p = 16.5 atm), the effect of ammonia content on the combustion and emission characteristics of laminar premixed methane flames was numerically investigated. This research uses the PREMIX code from ANSYS CHEMKIN-PRO 2020 and Okafor chemical kinetic mechanisms and provides a reference for our subsequent analysis of gas turbine operating conditions. Firstly, the emission data of major pollutants under different ammonia content (XNH3 = 0–1.0) and equivalent ratio (Φ = .6–1.4) were calculated. Then, the laminar premixed flame structure is analyzed under the lean fuel conditions associated with gas turbines (Φ = .6, .8). Finally, the effect of ammonia addition on the chemical reaction path of NO and CO emission was studied. The results show that ammonia/methane mixture fuel is more suitable for combustion at .6 < Φ < .8 under high temperature and pressure. High ammonia content (XNH3 > .6) and low equivalent ratio can reduce NO and CO emissions. The molar fractions of H, O, and OH radicals and flame temperature decreased with the increase in ammonia content. In addition, high temperature and high pressure conditions and ammonia content greatly influence the reaction path of NO and CO production. The increase in pressure resulted in a change in the primary reaction that produced NO. In conclusion, this study guides reducing the emission of NO and CO from lean side of gas turbine plants.